2008
DOI: 10.1021/la802556e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Thermoresponsive Polymer Gradients for Study of Cell Adhesion and Detachment

Abstract: A poly(N-isopropylacrylamide) (PNIPAAm) gradient covalently anchored on a silicon substrate with a linear variation of thickness was fabricated by continuous injection of the reaction mixture (NIPAAm, CuBr and its ligand, methanol, and water) into a glass chamber containing a silicon wafer, whose surface had been homogeneously immobilized with bromoisobutyryl bromide (BIBB). Because of the good control of the surface-initiated atom transfer radical polymerization (SI-ATRP) technique, the thickness of the PNIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 62 publications
9
103
0
Order By: Relevance
“…[60] This phenomenon was also observed for PNIPAAm brushes grafted on silicon and tissue-culture polystyrene (TCPS) surfaces. [61,62] Thermo-responsive cell adhesion/detachment behavior was found to weaken or even disappear when the PNIPAAm layer thickness was beyond a ''critical'' value.…”
Section: Stimuli-responsive Polymers and Diblock Copolymers For Surfamentioning
confidence: 99%
“…[60] This phenomenon was also observed for PNIPAAm brushes grafted on silicon and tissue-culture polystyrene (TCPS) surfaces. [61,62] Thermo-responsive cell adhesion/detachment behavior was found to weaken or even disappear when the PNIPAAm layer thickness was beyond a ''critical'' value.…”
Section: Stimuli-responsive Polymers and Diblock Copolymers For Surfamentioning
confidence: 99%
“…As shown in Figure 5b, the cells did not exist on the surface of the silica-HBPS-g-PNIPAM at either 37 or 25 1C. According to the literature regarding PNIPAM-grafted-silicon substrates, 23 cell adhesion onto and detachment from PNIPAM-modified substrates did not work well when the thickness of the grafted PNIPAM was insufficient. The short length of grafted PNIPAM forms into a dense film structure on the surface of the substrate.…”
Section: Pnipam (mentioning
confidence: 86%
“…Other groups reported that plasma activation and plasma polymerization were also available for the surface modification with PIPPAm [41]. Recently, to precisely control chain length and density of grafted PIPAAm on the surfaces, atom transfer radical polymerization (ATRP) or reversible addition-fragmentation chain transfer (RAFT) polymerization are also used, which contributes to enhanced handling of cell attachment or detachment [42][43][44][45][46]. Furthermore, we have also developed the method to fabricate a cell sheet using the thermoresponsive surfaces that are prepared via a spin-coating method with a block copolymer consisting of PIPAAm and poly(butyl methacrylate) (PBMA) on polystyrene surfaces [47].…”
Section: Cell Sheet Engineering Based On Temperatureresponsive Culturmentioning
confidence: 99%